Promoting 21st Century Skills in English Language Teaching: A Pedagogical Transformation in Ivory Coast - Paschal, Mahona Joseph; Gougou, Saman Ange-Michel (Global Journal of Educational Studies, 2024)
This study intended to understand English teachers’ experiences through 21st century skills in English Language Teaching (ELT) for a pedagogical transformation. In the world, many teaching challenges that negatively affect the English Language Teaching (ELT) effectiveness could be teaching approach, class size, technology integration, multilingualism, teaching resources, and opportunities of practices. Thus, the integration of the 21st century skills encounter some contextual challenges. The study used qualitative approach and a case study design to investigate the experiences of English Language teachers in Ivory Coast, a West Africa francophone country. Through a constructivist perspective, this case study applies the semi directive interview to evaluate the integration of 21st pedagogical skills in ELT in the Ivorian context. Participants used in this study were teachers’ educators from public schools, private schools, vocational and independent educative institutions to understand the ELT experience in various context. Findings revealed that 21st Century pedagogy is promoting in Teachers practices and that results in positive learning engagement. Yet, many contextual challenges and issues affect the effectiveness of ELT. The study recommended that a pedagogical transformation requires a communicative approach and lifelong learning to provide opportunities to update teaching and learning strategies for an effective language skills acquisition by all the learners and education system stakeholders.